Coexisting Disorders and Problems in Preschool Children with Autism Spectrum Disorders - Höglund Carlsson, Lotta (Hindawi Publishing Corporation, 2013)
Objectives. To analyze cooccurring disorders and problems in a representative group of 198 preschool children with autism spectrum disorders (ASD) who had had interventions at a specialized habilitation center. Methods. Parents and children were seen by a research team. Data were based on parental interviews, pediatric assessments, and tests of the child. Information on autistic symptoms, general cognitive function, speech and language, motor function, epilepsy, vision, hearing, activity level, behavior, and sleep was collected. Results. Three ASD categories were used: (1) autistic disorder (AD), (2) autistic-like condition (ALC) or Asperger syndrome, and (3) one group with autistic symptoms/traits but not entirely all its criteria met for ASD. Children with autism had a mean of 3.2 coexisting disorders or problems, the ALC/Asperger group had a mean of 1.6, and children with autistic traits had a mean of 1.6. The most common disorder/problems in the total group pertained to language problems (78%), intellectual disability (ID) (49%), below average motor function (37%), and severe hyperactivity/ADHD (33%). Conclusions. The results accord with the concept of early symptomatic syndromes eliciting neurodevelopmental clinical examination (ESSENCE), and highlight the need of considering ASD in a broad perspective taking also other cooccurring developmental disorders into account.